A study of the sensitivity of biomechanical models of the spine for scoliosis brace design. (August 2021) - Koutras, Christos; Pérez, Jesús; Kardash, Kateryna; Otaduy, Miguel A.
Highlights: Sensitivity analysis in the human's torso mechanical elements. Definition of parameters estimation criteria for the human's torso. One step towards the development of personalized biomechanical models. Contribution to computational solutions for the design of scoliosis braces. Abstract: Background and Objective: The development of biomechanical models of the torso and the spine opens the door to computational solutions for the design of braces for adolescent idiopathic scoliosis. However, the design of such biomechanical models faces several unknowns, such as the correct identification of relevant mechanical elements, or the required accuracy of model parameters. The objective of this study was to design a methodology for the identification of the aforementioned elements, with the purpose of creating personalized models suited for patient-specific brace design and the definition of parameter estimation criteria. Methods: We have developed a comprehensive model of the torso, including spine, ribcage and soft tissue, and we have developed computational tools for the analysis of the model parameters. With these tools, we perform an analysis of the model under typical loading conditions of scoliosis braces. Results: We present a complete sensitivity analysis of the models mechanical parameters and a comparison between a reference healthy subject and a subject suffering from scoliosis. Furthermore, we make a direct connection between error bounds on the deformation and tolerances for parameter estimation, which can guide the personalization of the model. Conclusions: Not surprisingly, the stiffness parameters that govern the lateral deformation of the spine in the frontal plane are some of the most relevant parameters, and require careful modeling. More surprisingly, their relevance is on par with the correct parameterization of the soft tissue of the torso. For scoliosis patients, but not for healthy subjects, we observe that the axial rotation of the spine also requires careful modeling.